THE EFFECTS OF PHYSICAL MOVEMENT ON LANGUAGE LEARNERS’ SELF-CONFIDENCE AND WILLINGNESS TO COMMUNICATE - Huynh, Thu-Nguyet; Nguyen, Long V. (VNU Journal of Foreign Studies, 2021)
In the light of Dynamic Systems Theory, which defines language development as an interaction of various factors in a system, a quantitative research was executed to examine the effects of physical movement in classrooms on students’ self-confidence (SC) and willingness to communicate (WTC) in English. Four groups of English-majored freshmen from a university in Vietnam were selected as participants for this study. In their English course on communication skills, namely listening and speaking, they were regularly encouraged to move within their classroom or the classroom’s vicinity to do oral tasks in pairs or groups. A survey was conducted to measure the difference in their SC and WTC. Findings revealed a positive correlation between SC and WTC. Besides, it recorded positive effects of level and scale of mindful physical movement on SC and WTC’s improvement. This is a preliminary study to propose a pedagogical method to solve the issue of crowded FL classrooms.